A simple synthesis of [RuCl2(NHC)(p-cymene)] complexes and their use in olefin oxidation catalysis. Issue 11 (1st March 2021) - Ma, Xinyuan; Guillet, Sébastien G.; Peng, Min; Van Hecke, Kristof; Nolan, Steven P.
Abstract : An operationally simple synthetic route is designed to access the [RuCl2 (NHC)( p -cymene)] family of complexes. Abstract : A simple and efficient synthetic route to [RuCl2 (NHC)( p -cymene)] and [Ru(CO3 )(NHC)( p -cymene)] complexes making use of a weak base, under aerobic conditions, is reported. This method enables access to a series of NHC-ruthenium compounds with moderate to good yields under mild conditions. The Ru pre-catalysts were successfully used in olefin oxidation catalysis at low catalyst loading and reach complete conversion in short times.